Prevalence and influencing factors of individuals at high risk of cardiovascular disease in 35 - 75 years old residents in Hebei province, 2016 - 2020: a cross-sectional survey - Yuhuan LIU; Jingjing ZHAO; Fujuan YUE; Lijuan TANG; Fan ZHANG; Xiaoli LIU; Dongsheng JIANG (Editorial Office of Chinese Journal of Public Health, 2024)
ObjectiveTo detect individuals at high risk of cardiovascular disease (CVD) and to explore influencing factors of the risk among 35 - 75-year-old residents in Hebei province for prevention and treatment of CVD in the population. MethodsTotally 140 632 permanent residents aged 35 - 75 years were recruited with stratified random cluster sampling in 11 districts/counties/prefectures covered by the CVD high-risk population screening and comprehensive intervention program across Hebei province. Face-to-face interview with a questionnaire designed by domestic researchers, physical examination, and detections of serum lipids and fasting blood glucose were conducted among the participants from September 2016 through November 2020. The CVD risk was evaluated based on any of the followings: history of cardiovascular and cerebrovascular diseases, hypertension, dyslipidemia and with 10-year risk of ≥ 20% for CVD assessed according the 'risk prediction charts' published by World Health Orgaization. The detection rate of individuals at high risk of CVD and influencing factors of CVD risk were analyzed. ResultsAmong the 137 115 participants (97.50% of all residents surveyed) with eligible responses, 33 297 (24.3%) were assessed as being at high CVD risk. The results of multivariate unconditional logistic regression analysis showed that aged 50 years and above, living in rural areas, smoking, hypertension, diabetes, dyslipidemia, and obesity were risk factors of having a high-risk of CVD, while, being female and with the education of junior middle school were protective factors against CVD risk among 35 - 75 years old residents in Hebei province. ConclusionThe proportion of individuals at high risk of CVD is relatively high and the risk is mainly influenced by gender, age, education, living residence, hypertension, diabetes, dyslipidemia, and obesity among 35 - 75-year-old residents in Hebei province.